2009
DOI: 10.3390/md7040689
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive and Anti-Inflammatory Activities of Caulerpin, a Bisindole Alkaloid Isolated from Seaweeds of the Genus Caulerpa

Abstract: The antinociceptive and anti-inflammatory activity of caulerpin was investigated. This bisindole alkaloid was isolated from the lipoid extract of Caulerpa racemosa and its structure was identified by spectroscopic methods, including IR and NMR techniques. The pharmacological assays used were the writhing and the hot plate tests, the formalin-induced pain, the capsaicin-induced ear edema and the carrageenan-induced peritonitis. Caulerpin was given orally at a concentration of 100 μmol/kg. In the abdominal const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 51 publications
2
74
0
2
Order By: Relevance
“…16 Além disso, conforme resultados anteriormente comentados, novos extratos foram testados e a caulerpina foi o princípio ativo responsável pela atividade anti-inflamatória e antinociceptiva observada nos extratos de Caulerpa racemosa e C. mexicana. [17][18][19] A atividade antioxidante de frações de Halimeda incrassata também foi estabelecida em estudos feitos por pesquisadores brasileiros, porém não foram isolados os seus princípios ativos. 20 Outras algas verdes foram avaliadas quanto ao seu potencial antioxidante, como, por exemplo, os extratos metanólicos de Codium decorticatum, Enteromorpha intestinalis, Ulva fasciata e Chaetomorpha antennina.…”
Section: Produtos Naturais De Algas Verdes Marinhasunclassified
“…16 Além disso, conforme resultados anteriormente comentados, novos extratos foram testados e a caulerpina foi o princípio ativo responsável pela atividade anti-inflamatória e antinociceptiva observada nos extratos de Caulerpa racemosa e C. mexicana. [17][18][19] A atividade antioxidante de frações de Halimeda incrassata também foi estabelecida em estudos feitos por pesquisadores brasileiros, porém não foram isolados os seus princípios ativos. 20 Outras algas verdes foram avaliadas quanto ao seu potencial antioxidante, como, por exemplo, os extratos metanólicos de Codium decorticatum, Enteromorpha intestinalis, Ulva fasciata e Chaetomorpha antennina.…”
Section: Produtos Naturais De Algas Verdes Marinhasunclassified
“…Their phytochemical properties elevate their potential value for the pharmaceutical industry (Yan et al 1998;Ganesan et al 2011). Seaweed extracts have various pharmacological properties including antioxidant Kannan et al 2013a), antimicrobial (Stirk et al 2007), anticancer, antinociceptive (De Souza et al 2009), photoprotective (Guinea et al 2012), antiinflammatory (De Souza et al 2009), antiacetylcholinesterase (Stirk et al 2007; Kannan et al 2013b); antidiabetic (Kannan et al 2013a), and antiviral (Hudson et al 1999) activities.…”
Section: Introductionmentioning
confidence: 96%
“…An example is caulerpenyne, a metabolite that showed cellgrowth inhibitory effects (Fischel et al 1995 ) , antiproliferative activity in tumor cell lines (Barbier et al 2001 ) , and has been suggested as a possible alternative source of antitumor drugs (Cavas et al 2006 ) . The metabolite caulerpin has also been reported to have many in vitro biological activities, such as antitumor, growth regulator, and plant root growth stimulant; recently, in vivo bioactivities such as anticonceptive (i.e., analgesic) and anti-infl ammatory have also been described (de Souza et al 2009 ) .…”
Section: The Genus Caulerpa Jv Lamourouxmentioning
confidence: 99%